Combination of Proteasome and Histone Deacetylase Inhibitors Overcomes the Impact of Gain-of-Function p53 Mutations - Meng, Xiangbing; Yang, Shujie; Li, Yujun; Li, Yiyang; Devor, Eric J.; Bi, Jianling; Wang, Xinhao; Umesalma, Shaikamjad; Quelle, Dawn E.; Thiel, William H.; Thiel, Kristina W.; Leslie, Kimberly K. (Disease Markers, 2018)
Mutations in the “guardian of the genome” TP53 predominate in solid tumors. In addition to loss of tumor suppressor activity, a specific subset of missense mutations confers additional oncogenic properties. These “gain-of-function” (GOF) mutations portend poor prognosis across cancer types regardless of treatment. Our objective in this study was to identify novel therapeutic opportunities to overcome the deleterious effects of GOF TP53 mutants. Using gynecologic cancer cell lines with known TP53 mutational status, we established that treatment with a proteasome inhibitor induced cell death in cells with two recurrent GOF TP53 mutations (R175H and R248Q), and addition of a histone deacetylase inhibitor (HDACi) enhanced this effect. By contrast, p53-null cancer cells were relatively resistant to the combination. Proteasome inhibition promoted apoptosis of cells with TP53 GOF mutations, potentially through induction of the unfolded protein response. In line with the reported hyperstabilization of GOF p53 protein, cells treated with HDACi exhibited reduced levels of p53 protein. Together, these data form the basis for future clinical studies examining therapeutic efficacy in a preselected patient population with GOF TP53 mutations.